Implementation of the CLCG Method in the Implementation of Final Semester Exams - Ramadhan, Fahri; Kurniawan, Helmi (Marqcha Institute, 2025)
The final semester examination is one of the essential instruments in measuring students’ competency achievement in schools. However, conventional exam implementation often faces challenges such as high operational costs, time-consuming correction processes, and the potential for cheating due to identical questions among students. This study aims to design and develop an Android-based examination application by implementing the Couple Linear Congruential Generator (CLCG) method as a question randomization mechanism. CLCG was chosen because it can generate random numbers with a more uniform distribution and longer period compared to the conventional Linear Congruential Generator (LCG), ensuring that each student receives a different set of questions while maintaining the same level of difficulty. The research was conducted at SMK Harapan Mekar 1 Medan using a prototype-based system development approach. The results show that the developed Android-based exam application runs effectively, successfully randomizes questions using the CLCG method, and facilitates teachers in managing the question bank and accelerating the grading process. Therefore, the application of the CLCG method in an Android-based digital exam system proves to improve efficiency, objectivity, and security in the implementation of final semester examinations in schools.